Investigasi Bidang Gelincir Zona Rawan Longsor dengan Metode Geolistrik di Sekitar Kawasan Wisata Panorama Bukittinggi - Mifthahul Putri; Elistia Liza Namigo (Universitas Andalas, 2024)
The investigation of the slip plane in the landslide-prone area around Taman Panorama, Kayu Kubu, Bukittinggi City has been conducted using the 2-dimensional resistivity geoelectric method with Wenner configuration.The study was carried out on hills with a slope of 40°. Data collection was conducted along three tracks with lengths of 80, 70, and 70 meters respectively. Data processing was done using Res2dinv software to display a 2-dimensional image of subsurface layers based on the measured resistivity values in the field. The interpretation of the data results showed the presence of slippage zones along each track in the form of an volcanic breccia rock layer. For line AB, resistivity values range from 250 to 813 Ωm at depths of 3.75 - 15.9 meters. Line CD has resistivity values ranging from 137 to 375 Ωm at depths of 3.75 - 15.9 meters, while track EF had resistivity values range from 183 – 287 Ωm at depths of 6.38 – 9.25 meters. Based on the depths, the identified slip surfaces are categorized as quite deep, thus this area is classified as a landslide-prone zone.